Context-Dependent Control of Erosion Resistance in Intertidal Flats: The Central Role of Bulk Density Across Natural and Restored Systems - Rafaela Paulo Teixeira; Laura Bossaer; Gregory S. Fivash; Tim Grandjean; Jim van Belzen; Johan van de Koppel; Stijn Temmerman; Tjeerd J. Bouma; Brenda Walles (Journal of Marine Science and Engineering, 2026)
Intertidal flats are highly dynamic coastal environments that provide vital ecosystem services. Despite their importance, intertidal flats are declining worldwide. In response, a range of restoration and management measures are increasingly being applied to enhance sediment accumulation and stabilize the bed surface. However, the effectiveness of these interventions ultimately depends on how sediment properties and bed stability develop over time. Quantitative understanding of these properties in natural and restored intertidal areas remains limited because field measurements are scarce, spatial heterogeneity is high, and hydrodynamic forcing is highly variable. Here, we quantify differences in key sediment properties between natural and restored intertidal flats to identify bed stability. We sampled sediments and measured key in situ bed characteristics at 16 intertidal sites in the Dutch Eastern and Western Scheldts, spanning multiple restoration strategies (i.e., managed realignments, groynes, and sediment nourishments) and natural locations. Our results show that restoration sites differ in sediment characteristics, with bulk density as the most consistent predictor of critical shear stress, an indicator of bed stability. These findings provide new insights into erosion thresholds in intertidal environments and can help inform adaptive coastal management of restoration measures under accelerating intertidal loss.

Short-Term Bed-Level Dynamics of an Intertidal Shoal After Large-Scale Nourishment - Tim J. Grandjean; Jim van Belzen; Daphne van der Wal; P. Lodewijk M. de Vet; Jeroen van Dalen; Jaco C. de Smit; Zhengquan Zhou; Johan van de Koppel; Tjeerd J. Bouma; Brenda Walles (Journal of Marine Science and Engineering, 2026)
Erosion and habitat loss on intertidal flats are increasingly fought through large-scale sediment nourishment. Yet the impact of nourishment on short-term bed-level dynamics remains poorly quantified. Daily erosion–accretion events shape the immediate physical environment experienced by benthic infauna: repeated burial and re-exposure set the physical bounds of the ecological niche, making bed-level dynamics a key indicator of habitat suitability that annual bathymetric surveys fail to capture. We evaluate the impact of a large-scale (1.13 million m3) nourishment at Roggenplaat in the Eastern Scheldt, Netherlands (2019) on bed-level dynamics, comparing daily bed-level changes between nourished and adjacent non-nourished areas with millimetre precision over five years. We assess three dimensions: persistence (temporal memory of the bed-level state), volatility (the frequency and magnitude of daily change), and sensitivity (the coupling between forcing and bed-level response). Two key insights emerge. First, nourished areas showed larger daily fluctuations, but event-driven bed-level changes were indistinguishable between treatments. Second, nourishment shifted the forcing balance: storm events dominate erosion in non-nourished areas, whereas in nourished areas, spring tides alone drive both accretion and erosion. Ecologically, the elevated daily disturbance is expected to act as a community-assembly filter, selecting for mobile infauna rather than excluding colonisation. These findings suggest that, although nourishment elevates day-to-day bed-level activity, its episodic disturbance regime remains compatible with the native bed-level regime, with implications for benthic habitat assessment at future restoration sites.

Skyglow increases cyanobacteria abundance and organic matter cycling in lakes - Jeremy Fonvielle; Lukas Thuile Bistarelli; Yile Tao; Jason N. Woodhouse; Tom Shatwell; Luis A. Villalba; Stella A. Berger; Christopher C.M. Kyba; Jens C. Nejstgaard; Andreas Jechow; Franziska Kupprat; Susanne Stephan; et al. (Water Research, 2025)

Sediment dynamics shape macrofauna mobility traits and abundance on tidal flats - Zhengquan Zhou; Tim J. Grandjean; Jaco de Smit; Jim van Belzen; Gregory S. Fivash; Brenda Walles; Olivier Beauchard; Jeroen van Dalen; Daniel B. Blok; Lennart van IJzerloo; Tom Ysebaert; Tjeerd J. Bouma (Limnology and Oceanography, 2024)
Tidal flats are valuable ecosystems that depend on complex biogeomorphic processes between organisms and sediment transport. Climate change has led to a rise in extreme weather events, such as storms. This, in turn, has increased sediment dynamics and created risks for the benthic communities inhabiting tidal flats. However, replicating sediment disturbances caused by extreme weather is difficult. To overcome this, we used the plow rake to enhance the natural tidal currents and wave conditions to simulate intensified sediment dynamics. The raking disturbance was repeated on two intertidal zones with different inundation frequencies and wind fetch levels to simulate the increasing frequency of storm impact on sediments due to climate change. We compared the measurements of sediment dynamics and macrofauna between plots that were raked and the control plots that were only influenced by natural hydrodynamics. Results showed that tidal flat sediments experienced erosion by 10–20 mm after six times biweekly raking treatments, depending on the site‐specific hydrodynamic conditions. Sediment dynamics served as a helpful tool for monitoring the species distribution regarding mobility traits: the high dynamic exposed sites were inhabited by mobile species, while the low dynamic sheltered sites were characterized by less‐mobile species. Moreover, the raking treatment decreased the abundance of species with immobile traits, yet the species composition did not experience significant change. Overall, the present findings indicate that tidal flats with low sediment dynamics and immobile macrofauna are at higher risk of declining abundance under intensified sediment disturbances than areas with high sediment dynamics and mobile macrofauna.

Lake browning counteracts cyanobacteria responses to nutrients: Evidence from phytoplankton dynamics in large enclosure experiments and comprehensive observational data - Anne Lyche Solheim; Hege Gundersen; Ute Mischke; Birger Skjelbred; Jens C. Nejstgaard; Alexis L. N. Guislain; Erik Sperfeld; Darren P. Giling; Sigrid Haande; Andreas Ballot; S. Jannicke Moe; Susanne Stephan; et al. (Global Change Biology, 2024)
Lakes worldwide are affected by multiple stressors, including climate change. This includes massive loading of both nutrients and humic substances to lakes during extreme weather events, which also may disrupt thermal stratification. Since multi‐stressor effects vary widely in space and time, their combined ecological impacts remain difficult to predict. Therefore, we combined two consecutive large enclosure experiments with a comprehensive time‐series and a broad‐scale field survey to unravel the combined effects of storm‐induced lake browning, nutrient enrichment and deep mixing on phytoplankton communities, focusing particularly on potentially toxic cyanobacterial blooms. The experimental results revealed that browning counteracted the stimulating effect of nutrients on phytoplankton and caused a shift from phototrophic cyanobacteria and chlorophytes to mixotrophic cryptophytes. Light limitation by browning was identified as the likely mechanism underlying this response. Deep‐mixing increased microcystin concentrations in clear nutrient‐enriched enclosures, caused by upwelling of a metalimnetic Planktothrix rubescens population. Monitoring data from a 25‐year time‐series of a eutrophic lake and from 588 northern European lakes corroborate the experimental results: Browning suppresses cyanobacteria in terms of both biovolume and proportion of the total phytoplankton biovolume. Both the experimental and observational results indicated a lower total phosphorus threshold for cyanobacterial bloom development in clearwater lakes (10–20 μg P L −1 ) than in humic lakes (20–30 μg P L −1 ). This finding provides management guidance for lakes receiving more nutrients and humic substances due to more frequent extreme weather events.

Diel vertical migration, size distribution and photoprotection in zooplankton as response to UV‐A radiation - Mikael T. Ekvall; Samuel Hylander; Tim Walles; Xi Yang; Lars‐Anders Hansson (Limnology and Oceanography, 2015)
The transparency regulator hypothesis (TRH) proposes that ultraviolet radiation (UVR) is a main driving force behind diel vertical migration (DVM) of zooplankton in clearwater systems. While previous studies have mainly studied DVM in relation to the TRH on a spatial scale across systems we here focus on long‐term trends in a single system in order to assess if UVR explains observed patterns in DVM. We show that the strength of DVM in Daphnia is to a large extent explained by UVR and we demonstrate a tipping point at which the UVR intensity drastically affects the strength of DVM in Daphnia . In contrast, the strength of DVM could not be explained by the level of UVR among calanoid copepods. The amount of photoprotective compounds did not differ between zooplankton found at different depths indicating that zooplankton do not change their vertical position in relation to the amount of accumulated photoprotective compounds. In addition, we show that both Daphnia and calanoid copepods display patterns of size structured migration.